FRI0036 Sustained remission related factors in patients with rheumatoid arthritis: is it possible to predict sustained remission?. (12th June 2018) - Yilmaz-Oner, S.; Gazel, U.; Can, M.; Atagunduz, P.; Direskeneli, H.; Inanc, N.
Abstract : Background: The management of RA have been changed during past decades and sustained remission (SR) is the ultimate goal to halt joint damage and prevent the accrual of disability. Factors predicting SR are essential to individualise treatment and recognise patients that have an opportunity to taper medications in daily practice. Objectives: To determine baseline predictors of sustained remission and comparison of its predictability by different remission criteria. Methods: A total of 428 consecutive patients with RA visiting our outpatient clinic routinely between September 2012–2013 were evaluated. Seventy seven of these patients satisfying the DAS28 remission (<2.6) within the time frame were enrolled and followed-up prospectively for 62.2±9.9 months. Of these fulfiling the DAS28 remission ≥6 months (sustained remission) and shorter (non-sustained remission:N-SR) were compared in terms of baseline demographic and clinical data and the presence of anxiety, depression, fibromyalgia and fatigue to determine possible predictors of SR. At enrollment, first and fifth years, the DAS28, SDAI and Boolean remission rates of patients were determined and compared with regard to DAS28 remission visit counts throughout the follow-up. We also assessed the difference between the SDAI and Boolean remission rates at initial, first and fifth years' visits. Results: Of these 77 patients, 63 were in SR and 14 were in N-SR. Lower baseline DAS28 and HAQ scores (p=0.045; p=0.026, respectively) and anti-CCP positivity (p=0.035) were positive predictors of SR. Although the presence of anxiety, depression, fibromyalgia and fatigue were lower in SR group, there was no statistical significance. DAS28 remission visit counts of patients in Boolean (n=32) and DAS28 (n=77) remission at enrollment (5.7±3.2 vs 5.4±3.1; p=0.995) were not different. Similarly, no difference was found between patients in SDAI (n=38) and DAS28 remission (5.6±3.3 vs 5.4±3.1; p=0.769). Patients meeting the DAS28 criteria (n=77, 100%) reduced 64% (n=50) at first and 42.6% (n=29) at fifth years. Patients satisfying SDAI and Boolean criteria were 49%, 44% vs 32.4% (n=22) and 41%, 28% vs 20.6% (n=14), respectively. If the duration of SR is considered as 6 months, the remission rates of SDAI were not different between patients at inclusion and fifth years but Boolean remission rates differed significantly and if it is accepted as ≥12 months, the SDAI and Boolean remission rates were not different than at fifth year visit. Conclusions: Low DAS28 and HAQ score at baseline and anti-CCP positivity were positive predictors of SR. Although the presence of anxiety, depression, fibromyalgia and fatigue were lower in SR group, there was no statistical significance. Compared to the DAS28, remission determined by the Boolean and especially SDAI criteria continued consistently in long term. References: [1] Castrejón I, Dougados M, Combe B, et al. Prediction of remission in a French Early Arthritis Cohort by RAPID3 and other core data set measures, but not by the absence of rheumatoid factor, anticitrullinated protein antibodies, or radiographic erosions. J Rheumatol. 2016Jul;43(7):1285–91. [2] Radner H, Alasti F, Smolen JS, et al. Physical function continues to improve when clinical remission is sustained in rheumatoid arthritis patients. Arthritis Res Ther. 2015Aug 11;17:203. Acknowledgements: None. Disclosure of Interest: None declared